Silver versus white sheet as a back reflector for microcrystalline silicon solar cells deposited on LPCVD-ZnO electrodes of various textures - Khazaka, Rami; Moulin, Etienne; Boccard, Mathieu; Garcia, Loïc; Hänni, Simon; Haug, Franz-Josef; Meillaud, Fanny; Ballif, Christophe (Progress in photovoltaics, 2015)
We compare the performance of two back reflector designs on the optoelectrical properties of microcrystalline silicon solar cells. The first one consists of a 5‐µm‐thick low‐pressure chemical vapor deposition (LPCVD)‐ZnO electrode combined with a white sheet; the second one incorporates an Ag reflector deposited on a thin LPCVD‐ZnO layer (with thickness below 200 nm). For this latter design, the optical loss in the nano‐rough Ag reflector can be strongly reduced by smoothing the surface of the thin underlying ZnO layer, by means of an Ar‐plasma treatment. Because of its superior lateral conductivity, the thin‐ZnO/Ag back reflector design provides a higher fill factor than the dielectric back reflector design. When decreasing the roughness of the front electrode with respect to our standard front LPCVD‐ZnO layer, the electrical cell performance is improved; in addition, the implementation of the thin‐ZnO/Ag back reflector leads to a significant relative gain in light trapping. Applying this newly optimized combination of front and back electrodes, the conversion efficiency is improved from 8.9% up to 9.4%, for cells with an active‐layer thickness of only 1.1 µm. We thereby highlight the necessity to optimize simultaneously the front and back electrodes. Copyright © 2014 John Wiley & Sons, Ltd. We show that smoothing the rear‐ZnO surface by means of an Ar‐based plasma treatment—prior to Ag deposition—was shown to drastically reduce plasmonic losses in Ag. In addition, the FF increases when replacing the thick‐LPCVD‐ZnO/air/WR by a thin‐ZnO/Ag BR design, thanks to the improved back‐electrode conductivity. By applying this newly optimized back electrode, the conversion efficiency is improved from 8.9% up to 9.3%. We also showed that a smoother front electrode leads to an amelioration of the electrical properties of the cell leading to an efficiency of 9.4%.